DECISION-MAKING BEHAVIOR OF WOMEN EXPERIENCING VIOLENCE: PSYCHOLOGICAL AND SOCIAL RESTRICTIONS (Scientific Conference on Multidisciplinary Studies, 2025)
This article examines the decision-making behavior of abused women, as well as the specific effects of psychological and social constraints on them. In addition, the article analyzes the decision-making processes of women who have been subjected to violence, such as avoiding violence, seeking legal assistance, or seeking social support